Optimizing YouTube Videos to Enhance English Listening Skills: Students’ Perceptions and Learning Strategies - Prayudha, Ananda Sabda; Pusparini, Indrawati (UIBU, 2024)
This study examines university students’ perceptions of using YouTube as a learning medium to improve English listening skills and explores how learners apply language learning strategies while engaging with YouTube content. Drawing on O’Malley and Chamot’s (1990) framework—metacognitive, cognitive, affective, and social strategies—this qualitative research involved ten English Department students from Sam Ratulangi University. Data were collected through semi-structured interviews and analyzed thematically. Findings reveal that students perceive YouTube as an effective, accessible, and motivating resource for developing listening skills due to its multimodal input, authentic language exposure, rich educational content, and convenience. Students reported improvements in comprehension, vocabulary, pronunciation, and awareness of accents. They also employed a range of learning strategies while using YouTube for language learning. The study concludes that YouTube functions as a powerful tool supporting autonomous listening development. Implications for teaching, learner autonomy, and future research are discussed